PENGEMBANGAN MEDIA ANIMATION SLIDE PRESENTATION UNTUK KEGIATAN PEMBELAJARAN FISIKA SECARA DARING PADA MATERI MEDAN MAGNET DI SMA - Susy Hardianti; Fakhruddin Fakhruddin; Zulirfan Zulirfan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Animation slide presentation learning media is a learning media packaged in the form of learning videos that allow students to always access the media anytime and anywhere because it is connected via the internet using google classroom and students can download the media after being uploaded by the teacher via google classroom. The media animation slide presentation in this study was developed on magnetic field material in high school. The purpose of this research is to produce learning media that are valid and can be used for teaching and learning physics activities in high school on magnetic field material. This research is expected to be a learning media that is easy to use and access by students so that learning objectives can be achieved even in online conditions. Besides, this media is expected to make it easier for teachers to deliver learning materials. This type of research is Research and Development (R&D) using the ADDIE model. This research is only limited to the development stage. The research instrument used in this study is the media validation assessment sheet and the material used by the validator to assess the appropriateness of using animation slide presentation media for teaching and learning activities. Data analysis in this study used quantitative data analysis, by calculating the average validity score of each validity indicator. The results showed that the media animation slide presentation was declared valid with the overall score of the media was 3.45 with a very high category, so it was declared feasible to be used in online physics teaching and learning activities on magnetic field material in high school.Keywords: Animation Slide Presentation Media, Online Learning, Magnetic Field